TGF-β prevents phosphate-induced osteogenesis through inhibition of BMP and Wnt/β-catenin pathways. - Fátima Guerrero; Carmen Herencia; Yolanda Almadén; Julio M Martínez-Moreno; Addy Montes de Oca; María Encarnación Rodriguez-Ortiz; Juan M Diaz-Tocados; Antonio Canalejo; Mónica Florio; Ignacio López; William G Richards; Mariano Rodriguez; et al. (PLoS ONE)
Background Transforming growth factor-β (TGF-β) is a key cytokine during differentiation of mesenchymal stem cells (MSC) into vascular smooth muscle cells (VSMC). High phosphate induces a phenotypic transformation of vascular smooth muscle cells (VSMC) into osteogenic-like cells. This study was aimed to evaluate signaling pathways involved during VSMC differentiation of MSC in presence or not of high phosphate. Results Our results showed that TGF-β induced nuclear translocation of Smad3 as well as the expression of vascular smooth muscle markers, such as smooth muscle alpha actin, SM22α, myocardin, and smooth muscle-myosin heavy chain. The addition of high phosphate to MSC promoted nuclear translocation of Smad1/5/8 and the activation of canonical Wnt/β-catenin in addition to an increase in BMP-2 expression, calcium deposition and alkaline phosphatase activity. The administration of TGF-β to MSC treated with high phosphate abolished all these effects by inhibiting canonical Wnt, BMP and TGF-β pathways. A similar outcome was observed in high phosphate-treated cells after the inhibition of canonical Wnt signaling with Dkk-1. Conversely, addition of both Wnt/β-catenin activators CHIR98014 and lithium chloride enhanced the effect of high phosphate on BMP-2, calcium deposition and alkaline phosphatase activity. Conclusions Full VSMC differentiation induced by TGF-β may not be achieved when extracellular phosphate levels are high. Moreover, TGF-β prevents high phosphate-induced osteogenesis by decreasing the nuclear translocation of Smad 1/5/8 and avoiding the activation of Wnt/β-catenin pathway.